2017
DOI: 10.1155/2017/8142032
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Wettability Modification and CO2 Solubility Effect by Carbonated Low Salinity Water Injection in Carbonate Reservoirs

Abstract: Carbonated water injection (CWI) induces oil swelling and viscosity reduction. Another advantage of this technique is that CO 2 can be stored via solubility trapping. The CO 2 solubility of brine is a key factor that determines the extent of these effects. The solubility is sensitive to pressure, temperature, and salinity. The salting-out phenomenon makes low saline brine a favorable condition for solubilizing CO 2 into brine, thus enabling the brine to deliver more CO 2 into reservoirs. In addition, low salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…19,111,145,146 A substantial increase in injectivity ranging from 35% to 170% was achieved from a simulation study. 145 Lee et al 146 also observed that carbonated low-salinity water flooding improved the relative injectivity of low-salinity water flooding (LSWF) from 0.83 to 0.86. In contrast, various permeability declines have been reported (Table 7).…”
Section: Injectivity Impairmentmentioning
confidence: 89%
See 1 more Smart Citation
“…19,111,145,146 A substantial increase in injectivity ranging from 35% to 170% was achieved from a simulation study. 145 Lee et al 146 also observed that carbonated low-salinity water flooding improved the relative injectivity of low-salinity water flooding (LSWF) from 0.83 to 0.86. In contrast, various permeability declines have been reported (Table 7).…”
Section: Injectivity Impairmentmentioning
confidence: 89%
“…Conversely, injectivity loss would engender insufficient CW injection pressure compared to reservoir pressure which could consequently lead to production decline or halt . A cluster of studies has underscored that CWI improves the injectivity of injection wells, which promotes oil recovery and efficient CO 2 storage in oil reservoirs. ,,, A substantial increase in injectivity ranging from 35% to 170% was achieved from a simulation study . Lee et al also observed that carbonated low-salinity water flooding improved the relative injectivity of low-salinity water flooding (LSWF) from 0.83 to 0.86.…”
Section: Consequence Of Geochemical Processes During Cwimentioning
confidence: 99%